PENGARUH METODE EKSTRAKSI TERHADAP KADAR FENOLIK DAN FLAVONOID TOTAL EKSTRAK TONGKOL JAGUNG (Zea mays L.) - Ramayani, Septiana Laksmi; Argadia, Mega; Purwati, Dyah Hayu (Media Farmasi Indonesia, 2016)
Abstract Corncobs is an agricultural waste having antioxidant activity because it contains phenolic and flavonoid compounds. One of the factors improving the quality of extract is slection of method extraction. Research aims to understand the influence of a method of extraction to the total phenolic and the total flavonoid contents in corncobs extract. The corncobs are macerated for three days and in reflux at the temperature 40°C for four hours. A solvent it used is ethanol 70 %. An extract obtained is determined for the total phenolic with the method Folin-ciocalteau using gallic acid as standart while levels flavonoid determined by the addition of reagent AlCl3 using Quersetin as a standart. Total phenolic content and total flavonoid content measured use of the spectrophotometer UV-Vis. The research results showed that of suggest reflux produce the total phenolic and the total flavonoid larger compared method maceration.The stastitical results using Independent t-Test showed that different method had significant to the total phenolic corncobs extract but not significantly to the total flavonoid contents in corncobs extract.